Feeding Value of Zizyphus Nummularia Leaves (Pala) for Lambs and Kids Fed With or Without Supplementation of Guar Meal - Thakur, S S; Mali, P C; Patnayak, B C; Lalchand, Lalchand (Annals of Arid Zone, 2016)
Fifteen weaner lambs and fifteen weaner kids were divided into three groups of five animals each. Within each species, group I was fed a control diet containing concentrate and chaffed Sewan (Lasillrlls sind:cIIs) hay. Group II was fed pala (Z. nummlllaria) leaves alone and group III was fed pala supplemented with guar (Cyamopsis tetragonoloba) meal. All groups were offered common salt freely. Blood samples were taken from each animal in the beginning and at the end of the experiment. The average daily gain over a 14 week period was 53.7 g/day in lambs and 22.1 g/day in kids in the control group while it was 15.0 g and 4.0 g on pala alone and 32.1 g and 27.5 g/day in gllar meal supplemented group. The overall average dry matter intake was 0.777 and 0451 kg/day in lambs and kids in control group, while on pala alone it was 0.656 kg and 0.44 kg and in pala supplemented with guar meal groups it was 0.711 kg and 0.530 kg. The dry matter intake per 100 kg body weight was 3.45 kg, 3.66 kg, and 3.46 kg in lambs and 3.17 kg, 3.73 kg and 3.81 kg in kids. respectively. There was no visual abnormality observed in the spleen, liver, rumen, reticulum, abomasum and small intestines of the animmals. Feeding of pula leaves reduced the blood inorganic phosphorus level and supplementation of gllar meal did not improve the level comparable to the control. The control group lambs and kids showed considerable increase in blood glucose level after the experimental feeding period. The feeding of pala leaves reduced blood glucose level in both the species. The blood urea level was reduced significantly in the pala fed kids. The supplementation of gllar meal maintained the pre-experimental level of urea in kids. The gllar meal supplementation could improve the feeding value of pala, but not to the extent comparable to that of control diet.